T60. SOCIAL MEDIA AND SOCIAL FUNCTIONING IN PSYCHOSIS: A SYSTEMATIC REVIEW. (9th April 2019) - Bjornestad, Jone; Hegelstad, Wenche ten Velden; Berg, Henrik; Davidson, Larry; Joa, Inge; Johannessen, Jan Olav; Melle, Ingrid; Stain, Helen J; Pallesen, Ståle
Abstract: Background: Social functioning impairment is a core predictor of outcome in psychosis and a main target for interventions. Assessments reflecting social reality are thus essential. After the 2004 advent of Facebook, social networking platforms have become integral to young peoples' social life and yet it is unclear whether this is being assessed. The aim of this systematic review is to examine the inclusion of social media activity in measures of social functioning in psychosis and ultra-high-risk for psychosis. Methods: Design: Systematic review. Data sources: Epistemonikos, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effect (DARE), MEDLINE, EMBASE and PsycINFO. Eligibility criteria for study selection: Empirical study published in English language in peer reviewed journals, with a sample meeting criteria (DSM/ICD) for a psychotic disorder or ultra-high risk for psychosis, and including a measure of social functioning. Papers published between January 2004 and April 2018 were included. Data extraction: The electronic search resulted in 10, 575 distinct articles. Full-text evaluation was conducted on 690 articles of which 573 articles met inclusion criteria. Results: 58 social functioning measures were identified. With some exceptions, reports on reliability and validity were scarce and only one measures integrated social media social activity. Discussion: The ecological validity of social functioning measures is challenged by the lack of assessment of social media activity as it fails to reflect an important aspect of the current social reality of persons with psychosis. Measures should be revised to include social media activity and thus avoid the clinical consequences of inadequate assessment of social functioning.